2021
DOI: 10.3390/nu13113913
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase Is Protective against the Multiomic Effects of a High Glycemic Diet on Brain Microvascular Inflammation and Cognitive Dysfunction

Abstract: Diet is a modifiable risk factor for cardiovascular disease (CVD) and dementia, yet relatively little is known about the effect of a high glycemic diet (HGD) on the brain’s microvasculature. The objective of our study was to determine the molecular effects of an HGD on hippocampal microvessels and cognitive function and determine if a soluble epoxide hydrolase (sEH) inhibitor (sEHI), known to be vasculoprotective and anti-inflammatory, modulates these effects. Wild type male mice were fed a low glycemic diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 81 publications
(112 reference statements)
0
19
0
Order By: Relevance
“…Recent approaches in the treatment of AD include exploring the potentials of some natural products with neuroprotective effects ( Kamil et al, 2018 , 2020 ; Prom-In et al, 2020 ; Kamal et al, 2021 ) and metabolites to modulate signaling pathways associated with neurovascular endothelium through multi-omic analyses ( Corral-Jara et al, 2021 ). There have also been reports on cellular signaling-related sex-dependent effects under hyperglycemic and lipid stress ( Nuthikattu et al, 2020 , 2021 ). However, this review focuses on significant signaling pathways associated with the stages of AD, the potential links between vascular dysfunction and AD, as well as recent developments in “omics”-based approaches in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches in the treatment of AD include exploring the potentials of some natural products with neuroprotective effects ( Kamil et al, 2018 , 2020 ; Prom-In et al, 2020 ; Kamal et al, 2021 ) and metabolites to modulate signaling pathways associated with neurovascular endothelium through multi-omic analyses ( Corral-Jara et al, 2021 ). There have also been reports on cellular signaling-related sex-dependent effects under hyperglycemic and lipid stress ( Nuthikattu et al, 2020 , 2021 ). However, this review focuses on significant signaling pathways associated with the stages of AD, the potential links between vascular dysfunction and AD, as well as recent developments in “omics”-based approaches in AD.…”
Section: Introductionmentioning
confidence: 99%
“…A HGD increases the levels of blood sugar and is associated with a higher risk of type 2 diabetes [ 30 ], cardiovascular diseases [ 30 , 31 ], and stroke [ 32 ]. We recently demonstrated in male mice that the HGD induces a detrimental transcriptomic response in the microvessels of the hippocampus [ 33 ], the region central to the formation of memory [ 34 ]. Our studies demonstrated changes in the transcriptome consistent with microvascular dysfunction, oxidation, inflammation, and alterations in mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the effects of the HGD on the brain and cognitive function showing that a HGD can contribute to vascular dysfunction and reduced cognitive function [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. We have shown deleterious effects of the HGD diet on the male brain microvasculature as a consequence of differential gene expression that is associated with hyperpermeability, apoptosis, and neurovascular inflammation [ 33 ]. Yet, only a few studies have addressed the response of the brain of females to a HGD [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuthikattu and colleagues [ 2 ] showed, using a multi-omic approach, that a high glycemic diet (HGD) leads to differential expression of 608 genes in vivo. HGD affected gene expression of brain microvessels in memory centers by up-regulating the protein-coding and non-coding genes involved in mitochondrial function, oxidation, inflammation, and microvascular functioning.…”
mentioning
confidence: 99%